EFEKTIVITAS PENGGUNAAN APLIKASI GOOGLE CLASSROOM PADA MATA KULIAH BELAJAR DAN PEMBELAJARAN TERHADAP HASIL BELAJAR MAHASISWA DI INSTITUT PENDIDIKAN TAPANULI SELATAN - Febriani Hastini Nasution; Nurhidaya Fithriyah Nasution; Muhammad Syahril Harahap (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The purpose of this research was to know the effectiveness of the use of google classroom application in “Belajar dan Pembelajaran” subject to students’ learning outcomes in Institut Pendidikan Tapanuli Selatan. The research method was quasi experiment with one group pre-test post-test design. The population was the entire of college students in fourth semester of Informatics Vocational Study Program which amount of student was 83 people. The sample of this research was the class IV-B totaling 27 people. The technique of sampling was cluster random sampling. The treatment was conducted was applying the Google Classroom application. The result of research was the use of google classroom application was effective in “Belajar dan Pembelajaran”subject to students’ learning outcomes in Institut Pendidikan Tapanuli Selatan, where the percentage value of <g> was 77.05 % in “effective” category.